Pengaruh Pengampunan Pajak dan Kemudahan Administrasi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Jakarta Penjaringan - M. Anjar Nurul Hayat (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Tax amnesty is a government policy program that provides an opportunity for taxpayers to pay their tax arrears without administrative sanctions in order to improve taxpayer compliance and state revenue. Given the importance of tax forgiveness programs in the implementation of government policies, especially in the implementation of self assessment system, it is interesting to examine how the implementation of tax capability is done by the Directorate General of Taxes in this case in the Tax Office Pratama Jakarta Penjaringan. In the preparation of this study, the authors use a quantitative approach, namely research that emphasizes the analysis on numerical data or numbers obtained by statistical methods and conducted on inferential research or in the framework of hypothesis testing so obtained the significance of the relationship between variables studied. The purpose of this study is to determine the implementation of tax pardons conducted by KPP Pratama Jakarta Penjaringan, ease of tax administration and changes in taxpayer compliance increase. The conclusion of research, that the implementation of tax amnesty and the ease of tax administration conducted by KPP Penjaringan in the period 2015-2017 have a strong influence on taxpayer compliance. The coefficient of determination (adjusted R2) shows the variable of Tax Amnesty (X1) and Ease of Tax Administration (X2) can explain or explain Personal Taxpayer Compliance KPP Pratama Jakarta Penjaringan (Y) of 28%. KPP is advised to improve tax administration system, service to Taxpayer, tax law enforcement and tax rate and intensive socialization to taxpayer about good tax administration knowledge.